The addition of submergence-tolerant sub1 gene into high yielding MR219 rice variety and analysis of its BC2F3 population in terms of yield and yield contributing characters to select advance lines as a variety - Ahmed, Fahim; Rafii, Mohd. Y.; Ismail, Mohd. Razi; Juraimi, Abdul Shukor; Harun, Abdul Rahim; Abdul Latif, Md.; Hasan, Mohammad Mahmudul; Tanweer, Fatah Abro (Taylor & Francis, 2016)
A cross was made between MR219 (high yielding but submergence intolerant) and Swarna-Sub1 (submergence tolerant) to produce submergence-tolerant rice variety using the marker-assisted backcrossing (MABC) method to protect the farmers of low-lying land from flash floods during rain. Knowledge of yield and yield contributing factors plays a vital role in the selection process of a variety. This experim ent was designed to determine the genetic diversity among recently produced different lines of BC2F3 population and also to compare all the lines with MR219 to find the best one. Agronomical, yield and yield contributing data were taken, while genotypic and phenotypic coefficients, variance components and heritability were estimated. Introgression of the target gene, Sub1, was done using tightly linked marker, and also background recovery was measured using simple sequence repeat (SSR) markers in different generations. The observed recurrent parent genome (RPG) recovery of BC2F2 generation was 95.37%, which indicates high-level similarity between the recurrent parent (MR219) and the resulting lines. Thirty newly developed lines of BC2F3 population, resulting backcross of MR219 and Swarna-Sub1, were planted with four replications following randomised complete block design (RCBD). Newly developed lines were grouped into four clusters based on traits with UPGMA dendrogram and cluster analysis to select the 10 best plants. This study will help the future researchers to select the best plants of a breeding programme after introgression of a gene considering phenotype performances to develop new varieties